(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2024)
This article discusses the work that needs to be done to ensure the rational use of the local budget of the Republic of Uzbekistan, to reduce poverty through the use of the local budget, to create new jobs and to improve the welfare of the population.